Indirect Method of Moisture Degree Evaluation in Varistors by Means of Dielectric Spectroscopy - Krzysztof Walczak (Energies)
Varistors, due to their unique properties, are materials commonly used in surge protection devices. Their reliability, however, requires periodic inspection, which should specifically include assessment of their moisture content. So far, no method has been developed that would directly and non-invasively allow for the assessment of the moisture content of a varistor. In this work, an attempt was made to use dielectric spectroscopy for this purpose, i.e., measurements of dielectric parameters in the frequency domain. The tests were carried out on samples of materials based on silicon carbide. The result of the tests was the determination of the dependence of the dielectric response of the tested materials on moisture content, which after further tests may be the starting point for the development of a method for determining the moisture content of varistor surge arresters.